Study on the effect of metabolites secondary of Streptomyces on the bacterium Pseudomonas aeruginosa isolated from dog’s wound - Raheem, Sara Abdulkareem; Abdalshheed, Dalia Abdalkareem (Revista de Ciências Agroveterinárias, 2024)
In Baghdad, Iraq, private veterinary clinics provided one hundred samples between February and December 2022. The study included 72 female and 28 male dogs with wound infections. Thirty isolates of P. aeruginosa were identified using biochemical assays and cultural traits. At Tikrit University, ten isolates of Streptomyces bacteria were discovered in soil samples collected from various locations in 2022. Biochemical testing and microscopic analysis were used to identify the isolates. Streptomyces secondary metabolites were subjected to an antibacterial activity assay at doses of 1024, 512, and 256μg/mL. The results illustrated that raw bacterial extract (Streptomyces spp.) exhibited considerable antibacterial activity against all isolates of P. aeruginosa. The results demonstrated that a concentration of 1024μg/mL was more efficient than 256μg/mL in combating P. aeruginosa. The susceptibility test of all P. aeruginosa isolates to 10 antibiotics was carried out by Kirby-Bauer method. The results demonstrated that all isolates were resistant to Ampicillin and Erythromycin (96.66%) followed by Ceftraxone (63.33%), Azithrofomycin (50%), Levofloxacin (46.66%), Cefotaxime, Ciprofloxacin and Gentamycin (43.33%), Ceftaziaime (26.66%) and Amikacin (6.66%). The results of the current study indicated that the majority of isolates with high resistance to antibiotics could be affected by Streptomyces secondary metabolites to expedite the healing of infected wounds.